2002
DOI: 10.1177/03635465020300051001
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis for Jumper's Knee in Male Athletes: Prospective Follow-up Study

Abstract: Jumper's knee causes mild but long-lasting symptoms after an athletic career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
189
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(195 citation statements)
references
References 18 publications
2
189
1
3
Order By: Relevance
“…Many factors have been suspected to predispose patients to this condition [2] by increasing the patellar tendon overload. The high chronic repetitive loading stimulates the local release of cytokines, with an autocrine and paracrine modulation of cell activity [14], that fails to adapt to continued abusive load and irritation and leads to intratendinous damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors have been suspected to predispose patients to this condition [2] by increasing the patellar tendon overload. The high chronic repetitive loading stimulates the local release of cytokines, with an autocrine and paracrine modulation of cell activity [14], that fails to adapt to continued abusive load and irritation and leads to intratendinous damage.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evaluations showed that the average duration of substantial pain problems and reduced function is nearly three years [1] and that at 15 years' follow-up 53% of the subjects reported quitting their sports career due to the damaged knee [2].…”
Section: Introductionmentioning
confidence: 99%
“…Prognosis is poor (Kettunen, Kvist, Alanen, & Kujala, 2002) and treatment strategy and effectiveness is debated (Cook & Khan, 2001;Larsson, Kall, & NilssonHelander, 2012;Visnes & Bahr, 2007). This highlights the importance of preventing the initial development of patellar tendinopathy, an approach that will most likely have to include restrictions in training volume (Visnes & Bahr, 2013), and possibly also in jump frequency (Bahr & Bahr, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In sports patients or professional athletes the impact on life and work is even greater, and the fast recovery of full efficiency and return to competition is of primary importance. Tissue repair in musculoskeletal injuries is often a slow and sometimes incomplete process, and the treatment options available may offer incomplete recovery and difficulties in returning to high activity level [2,3].…”
Section: Introductionmentioning
confidence: 99%